Pengaruh Kompetensi, Independensi dan Pengalaman Auditor terhadap Kualitas Audit dengan Etika Auditor sebagai Variabel Moderasi - Sekar Rika Namira Anjani; Fera Damayanti; Helisa Noviarty (Jurnal Syntax Admiration, 2024)
Auditor ability, independence, and experience are elements that can have an impact on audit quality; this study focuses on auditor ethics as moderation. Auditors working in the West Kalimantan Provincial Inspectorate Office are the subject of this study. A sample of 35 people who answered was collected by purposive sampling method. This study uses primary data through distributing questionnaires to respondents. Descriptive statistical tests, validity, reliability, normality, multicolinerity, heteroscedasticity, coefficient of determination, F, and t tests were performed on each variable using SPSS 25. The results of this study are the effect of auditor ability is not related to audit quality, independence factors and auditor experience are positively related to audit quality. And auditor ethics cannot moderate the factors of competence, independence and auditor experience on audit quality.